Critical analysis on exegetical methods in feminist edges of the Quran and the relavance of feminist Quranic scholarship with the Malaysian context - Wani Atiqah Binti Razemi (Program Pascasarjana Universitas Islam Negeri Sunan Kalijaga, 2023)
et,1/irh,c.1